Frontline Employee Feedback-Seeking Behavior: How Is It Formed and When Does It Matter? - USLU, AYPAR (SAGE PUBLICATIONS INC, 2019)
This research comprises two studies that extend the literature on the proactive behavior of feedback seeking. Study 1 uses cross-sectional data from frontline employees across 51 apparel stores to examine how feedback seeking is formed and under what conditions. The results suggest that the development of feedback-seeking behavior is contingent on a feedback-seeking climate and the relationship between an employee and his or her supervisor. Study 2 uses longitudinal data collected across three time periods from multiple respondents (i.e., frontline employees and managers) not only to replicate the findings from Study 1 but also to explore when feedback seeking matters. The findings reveal that managers should target employees who are less (vs. more) satisfied with their jobs because such employees perceive more instrumental value from feedback as a means to improve customer service and sales performance. The findings from this research provide insights that managers can use to increase feedback-seeking behavior from employees and effectively identify and manage the conditions under which feedback seeking will occur to greater or lesser degrees.
Keywords: feedback-seeking behavior; leader-member exchange (LMX); frontline em3ployee performance; feedback-seeking climate; job satisfaction; LEADER-MEMBER EXCHANGE; SELF-EFFICACY; METHOD BIAS; SERVICE; CLIMATE; MULTILEVEL; PERFORMANCE; REGRESSION; MODELS; SUBSTITUTES